Gambaran Parasit Cacing Nematoda Usus Dan Cestoda Pada Feses Sapi (Boss sp.) Di Peternakan Sumber Jaya Ternak, Kecamatan Tikung, Kabupaten Lamongan, Jawa Timur - Anindita Riesti Retno Arimurti (Universitas Muhammadiyah Surabaya, 2020)
Cows are important animals for Indonesian farmers who have high economic value. Cow breeding business has many benefits for human life, especially meat, milk, bones, skin, offal and feces (cow dung). Cow feces can be used as an organic fertilizer manufacture by cattle farmers. But it needs to be considered in making organic fertilizer derived from cows because it contains many diseases and parasites. If the cow's feces are not treated properly, it will cause environmental pollution to the local residents. Cow infected with parasites can experience a decrease in body weight, decreased endurance, impaired growth and death. To find out intestinal helminth parasitic infections, one of them is by identifying worms in cow feces. The majority of the population of Tikung Subdistrict, Lamongan Regency, earn their living as farmers and ranchers. The purpose of this study was to identify intestinal Nematode worms in cow feces in Tikung Subdistrict, Lamongan Regency. The method used in this study was Nacl Saturated to determine the morphology and forms of parasites. The results showed that cattle feces samples taken from the Tikung Subdistrict of Lamongan District contained the Nematoda parasite, which was found the presence of Hookworm eggs in 3 samples with a percentage of 6% and found 1 positive sample (+) containing Taenia saginata eggs, with a percentage of 2% of the total 50 samples in Sumber Jaya Livestock Farm in cattle on Tikung Subdistrict, Lamongan Regency is still relatively low. Keywords: Cow Feces (Bos sp.), Intestinal Nematodes, Cestodes